Benign prostatic obstruction (BPO) as a possible risk factor for Peyronie's disease (PD). The influence of BPO and PD on mental health - Gianni Paulis; Andrea Paulis (Archivio Italiano di Urologia e Andrologia, 2023)
To the Editor, Our study aimed to investigate a possible relationship between benign prostatic obstruction (BPO) and Peyronie's disease (PD) and to characterize the psychological profile of patients affected by Peyronie's disease, with or without concomitant BPO. In this study, we have investigated whether there is a relationship between the two diseases. The typical symptoms of PD are as follows: penile deformation, local pain, erectile dysfunction (ED), and anxious depressive state. Benign prostatic hyperplasia (BPH) causes symptoms only in the case of urinary obstruction (benign prostatic obstruction/BPO). BPO is an emotionally stressful condition, but any type of treatment, such as surgery, by significantly decreasing LUTS, can significantly improve the general well-being of the affected patient (1). We performed a retrospective analysis of the clinical database of a single uro-andrology clinic. From the database, we considered two separate cohorts of patients observed between January 2013 and February 2023. The first cohort included 539 patients diagnosed with Peyronie's disease. As a comparator population, we considered a cohort of 2208 outpatients referred to our clinic for any disease, but not Peyronie's disease. [...]